Effects of planting patterns plastic film mulching on soil temperature, moisture, functional bacteria and yield of winter wheat in the Loess Plateau of China - Xiao-dong ZHAO; Xiao-rui QIN; Ting-liang LI; Han-bing CAO; Ying-he XIE (Journal of Integrative Agriculture, 2023)
The yield of winter wheat is hindered by drought and low temperature in the Loess Plateau of China. Two common mulching methods to conserve soil moisture, ridge furrows with plastic film mulching (RP) and flat soil surfaces with plastic film mulching (FP) are helpful for wheat production. Our previous study indicated that FP could improve wheat yield more effectively than RP, but the reason remains unclear. The effect of mulching method on functional bacteria also needs to be further studied. In this study, winter wheat was employed to evaluate the impacts of mulching method on soil temperature, moisture content, microorganisms and grain yield. The results showed that FP had a warming effect when the soil temperature was low and a cooling effect when the temperature was too high. However, the ability to regulate soil temperature in the RP method was unstable and varied with year. The lowest negative accumulated soil temperature was found in the FP treatment, which was 20–89 and 43–99% lower than that of the RP and flat sowing with non-film mulching control (NP) treatments, respectively. Deep soil moisture was better transferred to topsoil for wheat growth in the FP and RP treatments than the NP treatment, which made the topsoil moisture in the two treatments (especially FP) more sufficient than that in the NP treatment during the early growing stage of wheat. However, due to the limited water resources in the study area, there was almost no difference between treatments in topsoil water storage during the later stage. The wheat yield in the FP treatment was significantly higher, by 12–16 and 23–56%, respectively, than in the RP and NP treatments. Significant positive correlations were observed among the negative accumulated soil temperature, spike number and wheat yield. The Chao1 and Shannon indices in the RP treatment were 17 and 3.9% higher than those in the NP treatment, respectively. However, according to network relationship analysis, the interspecific relationships of bacteria were weakened in the RP treatment. Phosphorus solubilizing, ammonification and nitrification bacteria were more active in the RP than in the FP treatment, and microbes with nitrate reduction ability and plant pathogens were inhibited in the RP treatment, which improved nutrient availability and habitat for wheat.